2014
DOI: 10.1007/s10096-014-2190-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of IL-2 for the diagnosis of latent tuberculosis: a systematic review and meta-analysis

Abstract: We conducted a systematic review and meta-analysis to evaluate the diagnostic potential of interleukin-2 (IL-2) as biomarkers for the diagnosis of latent tuberculosis. Related studies were identified through searches of PubMed, Embase, Web of Science, and complementary manual searches up to December 30, 2013. We used standard methods recommended for meta-analyses of diagnostic test evaluations. The analysis was based on a summary receiver operating characteristic (SROC) curve. Meta-regression analysis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…All these selected cytokine/chemokines are known to play a major role in TB diagnostics. Previous reports show that IFN-c, IL-6, IL-8 [11,19], IL-10, IL-12p40 [20] and IL-2 [21] were associated with LTBI. On the other hand, TNF-a [22,29], IP-10 and MCP-2 [9] were more associated with active TB.…”
Section: Discussionmentioning
confidence: 87%
“…All these selected cytokine/chemokines are known to play a major role in TB diagnostics. Previous reports show that IFN-c, IL-6, IL-8 [11,19], IL-10, IL-12p40 [20] and IL-2 [21] were associated with LTBI. On the other hand, TNF-a [22,29], IP-10 and MCP-2 [9] were more associated with active TB.…”
Section: Discussionmentioning
confidence: 87%
“…This study evaluated the diagnostic performance of IL-2 following stimulation with recombinant PE35 and PPE68 for the discrimination of active and latent TB. According to our previous meta-analysis, the sensitivity of the IL-2 assay following stimulation with TB antigen of QFT-G-IT test for diagnosis of LTBI ranged from 43 to 100 %, and the specificity of this marker was in the range from 89 to 100 % [31]. The pooled values of sensitivity (0.81) and specificity (0.95) showed the favorable accuracy of IL-2 for the detection of LTBI [31].…”
Section: Discussionmentioning
confidence: 96%
“…Among those IFNc and IL-2 T helper-1 (Th1) cytokines are of key importance for effective control of M. tuberculosis [25]. Several studies have demonstrated that IL-2 release, after stimulation by TBspecific antigens, was significantly higher in infected patients with TB than healthy controls [26][27][28][29][30], and suggested that IL-2 could be a potential biomarker for diagnosing LTBI infection [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 No definite risk factors were identified in this study however the total number of recurrences is too small for accurate statistical analysis. Local HIV prevalence is up to 3.8 per 1000 10 with black Africans being at greater risk; the majority of the patients are South Asian.…”
mentioning
confidence: 79%